Relating person‐centredness to quality‐of‐life assessments and patient‐reported outcomes in healthcare: A critical theoretical discussion. (3rd May 2022) - Andersson, Viktor; Sawatzky, Richard; Öhlén, Joakim
Abstract: Engagement with the historical and theoretical underpinnings of measuring quality of life (QoL) and patient‐reported outcomes (PROs) in healthcare is important. Ideas and values that shape such practices—and in the endgame, people's lives—might otherwise remain unexamined, be taken for granted or even essentialized. Our aim is to explicate and theoretically discuss the philosophical tenets underlying the practices of QoL assessment and PRO measurement in relation to the notion of person‐centredness. First, we engage with the late‐modern history of the concept of QoL and the act of assessing and measuring it. Working with the historical method of genealogy, we describe the development of both QoL assessments and PRO measures (PROMs) within healthcare by accounting for the contextual conditions for their possibility. In this way, the historical and philosophical underpinnings of these measurement practices are highlighted. We move on to analyse theoretical and philosophical underpinnings regarding the use of PROMs and QoL assessments in clinical practice, as demonstrated in review studies thereof. Finally, we offer a critical analysis regarding the state of theory in the literature and conclude that, although improved person‐centredness is an implied driver of QoL assessments and PROMs in clinical practice, enhanced theoretical underpinning of the development of QoL assessments is called for.